THE LEADERSHIP STRATEGY OF THE SCHOOL PRINCIPAL IN IMPROVING TEACHERSâ PERFORMANCE IN SMA MUHAMMADIYAH 4 SURABAYA - Mariyati, Siti (Studia Religia, 2018)
AbstractThe senior high school of Muhammadiyah 4 Surabaya is a school continuallyexperienced various developments including in an effort to improve theperformance of the teachers. SMA Muhammadiyah 4 Surabaya is a religion-based school in Karangpilang which experiences increasing number ofstudents and community interest from year to year. It cannot be separatedfrom the strategy and active role of the principal. This study aims to find outand explore what is the leadership strategy of school principals in improvingteachersâ performance in SMA Muhammadiyah 4 Surabaya? And what are thesupporting factors and obstacles of school principals in improving teachersâperformance in SMA Muhammadiyah 4 Surabaya? This is a qualitative researchwith descriptive approach. The process of data collection is done by usingobservation, interview and documentation. Data are collected and analyzedthrough several stages including data collection, reduction, and presentationthen drawing conclusions in accordance with the scope of the problem. Asthe findings of this study, it can be concluded that: First, Principal LeadershipStrategy in improving teacher performance in SMA Muhammadiyah 4Surabaya consists of 9 strategies. Second, the supporting factors in this schoolenvironment consist of 3 factors and the inhibiting factors consist of 2 factors.The supporting factors are teacher education level, conducive climate, andmental condition of the teachers. The inhibiting factors are caused by internaland external factors. The internal factor is budget limitation while the externalfactor is the parentsâ financial conditions.Â Keywords: Strategy, Leadership, Teachersâ Performance